DUB and its Homoeopathic Approach with Case Discussion (Advancements in Homeopathic Research, 2022)
As we know that irregular menstruation is very common in females now a days. And most of them are without any pelvic pathology that is dysfunctional uterine bleeding. As we know homoeopathy plays an important role in female menstrual disorders and we are not much dependent on diagnosis. We treat the patient not the disease. So here I am going to discuss how homeopathy acts wonderfully in case of Dysfunctional Uterine Bleeding.
Keywords: Dysfunctional Uterine Bleeding; homoeopathy